“Queremos mais histórias indígenas e Xavante” : leituras de estudantes Xavante sobre os indígenas no livro didático de História - Barroso, Mírian Regina Camargo (2020)
ABSTRACT: The aim of this work was to investigate the reading practices of the history textbook of Xavante students from Campinápolis-MT. The specific objectives were: 1) to analyze the indigenous issue in Brazilian history textbooks; 2) to investigate the history and culture of the Xavante; 3) to analyze the reading practices of the Xavante students' textbook. Methodologically, the work is based on the participating research according to Elsie Rockwelle and Justa Ezpeleta. Also in teaching techniques of Celestin Freinet's pedagogy. Theoretically the analysis was based on the debates of the New Cultural History, especially the concept of representation from Sandra Jatahy Pesavento and Roger Chartier. Initially we conducted a brief state of the art on the field of research in textbooks and the representations of indigenous ethnic groups in history textbooks. In a second moment we tried to present the field of research and get to know the history and culture of the Xavante. Finally, we carry out empirical research with Xavante high school students from a state school in Campinápolis-MT. The product was the production of the mural newspaper as a research technique to record the students' reading of the history textbook. The results express a critical reading of the representations of the indigenous ethnic groups in the history textbook, which indicates the absence of the Xavante culture and history.